2019
DOI: 10.1111/cas.14221
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and characterization of a novel neuroendocrine carcinoma cell line derived from a human ascending colon tumor

Abstract: The incidence of rare neuroendocrine tumors (NET) is rapidly increasing. Neuroendocrine carcinoma (NEC) is a NET with poorly differentiated histological features, high proliferative properties and associated poor prognoses. As these carcinomas are so rare and, thus, affect only a small number of patients allowing for few cell lines to be derived from patient biopsies, the histological, immunohistochemical, and clinical characteristics associated with colorectal NEC and NEC in other organs have yet to be clearl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 29 publications
(38 reference statements)
0
9
0
Order By: Relevance
“…Shinji et al recently established a novel cell line (SS-2) derived from resection of an ascending colon tumour (Shinji et al 2019). The SS-2 cell line maintained characteristic features of the resected tumour, which were also retained when implanted into the s.c. tissue of nude mice, and the authors concluded that these cells may add to the current knowledge of the biological behaviour of midgut NEC and thus may provide a novel therapeutic examination platform (Shinji et al 2019).…”
Section: Future Directionsmentioning
confidence: 99%
“…Shinji et al recently established a novel cell line (SS-2) derived from resection of an ascending colon tumour (Shinji et al 2019). The SS-2 cell line maintained characteristic features of the resected tumour, which were also retained when implanted into the s.c. tissue of nude mice, and the authors concluded that these cells may add to the current knowledge of the biological behaviour of midgut NEC and thus may provide a novel therapeutic examination platform (Shinji et al 2019).…”
Section: Future Directionsmentioning
confidence: 99%
“…CD133 is a robust biomarker to identify primary CSC and can be proposed as a prognostic marker of CRC patients. Moreover, it is reported to be expressed in poorly-differentiated NECs and well-differentiated NETs of the digestive tract [ 34 ] and was demonstrated to be expressed in CCSC-lines [ 35 ]. It is the most well-known marker for the isolation and investigation of CSC in different types of cancer [ 36 , 37 , 38 ] and known to be responsible for radio- and chemotherapy-resistance in CCSC [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In ascending colon cancer, WB can be useful for the determination of the presence and size of insulinoma-associated protein 1 (INSM-1) from lysates. INSM-1 is a product of gene INSM-1 that regulates the expression of neuroendocrine markers (Shinji et al, 2019).…”
Section: Western Blotmentioning
confidence: 99%
“…Moreover, RT-qPCR is commonly used as quality control to examine changes in expression during RNA sequencing (RNA-seq) (Adams, 2020). In the characterisation of cell lines, RT-qPCR can be used to investigate cancer stem cell markers, such as expression of clusters of differentiation (CD24, CD44, CD133, and CD166) (Shinji et al, 2019). This method also enables the detection of particular genes needed for cell line characterisation, for example, B2M and RPL29, in the case of tongue carcinoma cell line (Wang et al, 2017).…”
Section: Rt-qpcrmentioning
confidence: 99%